Therapeutic correction of ApoER2 splicing in Alzheimer's disease mice using antisense oligonucleotides - Anthony J Hinrich; Francine M Jodelka; Jennifer L Chang; Daniella Brutman; Angela M Bruno; Clark A Briggs; Bryan D James; Grace E Stutzmann; David A Bennett; Steven A Miller; Frank Rigo; Robert A Marr; et al. (EMBO Molecular Medicine)
Abstract Apolipoprotein E receptor 2 (ApoER2) is an apolipoprotein E receptor involved in long‐term potentiation, learning, and memory. Given its role in cognition and its association with the Alzheimer's disease (AD) risk gene, apoE, ApoER2 has been proposed to be involved in AD, though a role for the receptor in the disease is not clear. ApoER2 signaling requires amino acids encoded by alternatively spliced exon 19. Here, we report that the balance of ApoER2 exon 19 splicing is deregulated in postmortem brain tissue from AD patients and in a transgenic mouse model of AD. To test the role of deregulated ApoER2 splicing in AD, we designed an antisense oligonucleotide (ASO) that increases exon 19 splicing. Treatment of AD mice with a single dose of ASO corrected ApoER2 splicing for up to 6 months and improved synaptic function and learning and memory. These results reveal an association between ApoER2 isoform expression and AD, and provide preclinical evidence for the utility of ASOs as a therapeutic approach to mitigate Alzheimer's disease symptoms by improving ApoER2 exon 19 splicing.